Biblical Theology of Life in the New Testament - Viljoen, Francois P. (Reformed Theology in Africa Series, 2021)
This publication deals with A Biblical Theology of Life based on the New Testament. It forms the second of a two volume publication on A Biblical Theology of Life. These two volumes trace the concept of life throughout Protestant canon, working with the final form of the biblical books in Hebrew (vol. 5) and Greek (vol. 6) Scripture. This is done by providing the reader with a book-by-book overview of this concept. This book concludes with a final chapter synthesising the findings of the respective investigations of the Old and New Testament corpora in order to provide a summative theological perspective of the development of the concept through Scripture. It is clear that life forms a central and continuous theme throughout the Biblical text. The theme begins with the living God that creates life, but is shortly followed by death that threatens life. Despite this threat, God sustains life and awakens life from death. The text concludes with the consummation depicting eternal life in the new heaven and earth. The biblical theological approach that has been taken entails a thematic approach as it investigates the concept of life, with contextual foci on what individual books of Scripture teach about life, joined diachronically with an investigation of the progressive use of the concept of life in Scripture, while providing a theology of Scripture as a whole investigating the concept of life in all sixty-six books of the Protestant canon